18 F]Fluorodeoxyglucose PET/CT and prediction of histopathological response to neoadjuvant chemotherapy for adenocarcinoma of the oesophagus and oesophagogastric junction - Harustiak, T; Zemanova, M; Fencl, P; Hornofova, L; Pazdro, A; Snajdauf, M; Salkova, E; Lischke, R; Stolz, A (The British journal of surgery, 2018)
BACKGROUND: The aim of this prospective study was to assess whether [18 F]fluorodeoxyglucose PET can be used to predict histopathological response early in the course of neoadjuvant chemotherapy in patients with adenocarcinoma of the oesophagus and oesophagogastric junction. METHODS: Following the PET response criteria in solid tumours (PERCIST 1.0) as a standardized method for semiquantitative assessment of metabolic response, FDG-PET/CT was performed before (PET1) and after (PET2) initiation of the first cycle of chemotherapy. The relative changes in the peak standardized uptake value (ΔSUL) and total lesion glycolysis (ΔTLG) between PET1 and PET2 were correlated with histopathological response, defined as less than 50 per cent viable tumour cells in the resection specimen. A receiver operating characteristic (ROC) curve analysis was used to identify the optimal cut-off value with the highest accuracy of histopathological response prediction. RESULTS: PET2 was performed a median of 16 (range 12-22) days after the start of chemotherapy. Some 27 of 90 patients who underwent surgery had a histopathological response. There was no association between the median ΔSUL or median ΔTLG and the histopathological response. A post hoc analysis in 47 patients with PET2 performed 16 days or less after the start of chemotherapy showed that ΔTLG, but not ΔSUL, was associated with the histopathological response (P = 0·009). The optimal cut-off value of ΔTLG was 66 per cent or more. CONCLUSION: FDG-PET/CT after the first cycle of chemotherapy does not predict histopathological response in patients with adenocarcinoma of the oesophagus and oesophagogastric junction.
Keywords: Adenocarcinoma; ROC Curve; Fluorodeoxyglucose F18; neoadjuvantní terapie; Humans; Esophagogastric Junction; lidé středního věku; Chemotherapy, Adjuvant; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; nádory jícnu; gastroezofageální junkce; fluorodeoxyglukosa F18; Antineoplastic Agents; výsledek terapie; senioři; lidé; adjuvantní chemoterapie; Esophageal Neoplasms; Adult; ženské pohlaví; Male; Middle Aged; Positron Emission Tomography Computed Tomography; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Neoadjuvant Therapy; protinádorové látky; adenokarcinom; ROC křivka; mužské pohlaví; prospektivní studie; radiofarmaka; PET/CT; Radiopharmaceuticals; Prospective Studies